Properties of Metal Matrix Composite of Aluminium 11.8% Silicon Reinforced with Different Particulates - Vijayaram, Thoguluva Raghavan (2006)
A composite material is a materials system composed of a mixture or combination of two or more micro or macro constituents that differ in form and chemical composition and which are essentially insoluble in each other. Metal matrix composites are engineered materials composed of an elemental or alloy matrix in which an insoluble second phasel reinforcer is embedded and distributed to achieve some property improvement. Particulate reinforced metal matrix composites constitute a major portion of these advanced materials. Aluminium-silicon alloys, as a matrix material, are characterized by lightweight, good strength-to-weight ratio, ease of fabrication at reasonable cost, high strength at elevated temperature, good thermal conductivity, excellent castability, good weldability, excellent corrosion resistance and wear resistance properties. Application of particulate reinforced composites in the aerospace, automotive, transportation and construction industries depends on the choice of cost affordable factor. In this research work, particulate reinforced metal matrix composites are processed by vortex method, a melt stirring liquid metallurgy technique. Four different particulates namely, graphite, combination of tungsten carbide and aluminium silicate for hybrid composite reinforcement, quartz and titanium carbide are used as second phase reinforcers for reinforcement in the matrix. Aluminium-1 1.8% silicon alloy is selected as the matrix material and the particulates are mixed in different weight fraction %. Slab composite castings are made by pouring the composite mixture in grey cast, steel and copper permanent-molds. Process parameters like pouring temperature, particulate preheating temperature, impeller blade speed and shape are optimized and composite castings containing different weight fraction % of particulate are made by permanent-mold casting process. Effects on different weight fraction % addition of particulate on the particulate distribution in aluminum-1 1.8% silicon alloy composites are studied. The processed particulate reinforced composites are subjected to mechanical tensile testing and the properties are determined for different type of particulate reinforcements in the aluminium-11.8% silicon alloy matrix. Besides, hardness, density, impact strength-charpy, fracture toughness, electrical resistivity, electrical conductivity, thermal diffusivity, thermal conductivity, thermal expansion coefficient measurements are performed by using the appropriate equipments and machines. Metallographic studies of the processed particulate composites are conducted by optical microscopy and photomicrographs are captured at different magnifications to reveal and examine the particulate distribution in the aluminium-1 1.8% silicon alloy matrix. SEM observation of the fracture surfaces of tensile tested, charpy impact tested specimens are performed to study the fracture mechanics and surface characteristics with the aid of captured SEM fractographs. Interfacial bonding features of the processed composites are also analyzed with the help of SEM. Besides, slab castings without particulate addition are made and compared with the results based on the properties and microstructural features, particularly for the uniformity of particulate distribution in the aluminum-1 1.8% silicon alloy base matrix. It is found that the properties of the processed particulate reinforced aluminium-1 1.8% silicon alloy matrix composites are superior to the cast monolithic aluminium-1 1.8% silicon alloy based on the above-mentioned properties studies. Photomicrographs of the processed composites based on the metallographic studies have confirmed the uniformity of particulate distribution in the aluminium- 1 1.8% silicon alloy matrix.